The Gut-To-Breast Connection - Interdependence of Sterols and Sphingolipids in Multidrug Resistance and Breast Cancer Therapy - Spassieva, Stefka; Bieberich, Erhard (Anti-Cancer Agents in Medicinal Chemistry, 2011)
Almost all classes of bioactive lipids such as cholesterol and cholesterol derivatives, phospholipids and lysophospholipids, eicosanoids, and sphingolipids are critically involved in tumorigenesis. However, a systematic analysis of the distinct tumorigenic functions of lipids is rare. As a general principle, lipids either act directly by binding to receptors and other cell signaling proteins in growth control, or indirectly by regulating membrane organization such as the formation of membrane microdomains (lipid rafts) that modulate receptor or other membrane protein function. Lipid rafts are known to be formed by cholesterol and the sphingolipids or ceramide derivatives sphingomyelin and glucosylceramide (cholesterol-sphingomyelin-glucosylceramide or CSG rafts). In this review, we discuss the interconnection of sphingolipids with cholesterol and its derivatives in breast cancer drug resistance. Bile acids are cholesterol derivatives that are first synthesized in the liver (primary bile acids) and then metabolized by intestinal bacteria giving rise to secondary bile acids. They activate farnesoid X receptor (FXR), which inhibits cholesterol conversion to primary bile acids and induces the expression of drug resistance proteins. We introduce a novel model by which bile acid-mediated activation of FXR may promote the formation of CSG lipid rafts that trans-activate drug resistance proteins in breast cancer. Since breast cancer stem cells express high levels of drug resistance proteins, our model predicts that serum bile acids promote breast cancer stem cell survival and metastasis. Our model also predicts that FXR antagonists in combination with sphingolipid biosynthesis inhibitors may be promising candidates for novel drugs in lipid therapy of breast cancer.
Keywords: sphingomyelin